Physical and mathematical modeling of Earth and environment processes : 3rd International Scientific School for Young Scientists, Ishlinskii Institute for Problems in Mechanics of Russian Academy of Science /: 3rd International Scientific School for Young Scientists, Ishlinskii Institute for Problems in Mechanics of Russian Academy of Science. (2018) - Unknown
No abstract available